O‐HEALTH‐EDU: A scoping review on the reporting of oral health professional education in Europe. (7th September 2020) - Dixon, Jonathan; Manzanares‐Cespedes, Cristina; Davies, Julia; Vital, Sibylle; Gerber, Gabor; Paganelli, Corrado; Akota, Ilze; Greiveldinger, Alyette; Murphy, Denis; Quinn, Barry; Roger‐Leroi, Valerie; Tubert‐Jeannin, Stephanie; et al.
Abstract: Introduction: The variability in oral health professional education is likely to impact on the management of oral health needs across Europe. This scoping review forms the initial part of a larger EU‐funded collaborative Erasmus + project, 'O‐Health‐Edu'. The aim of this scoping review is to investigate how oral health professional education in Europe is reported. Methods: The PRISMA and Arksey & O'Malley methodological frameworks for scoping reviews were used to guide reviewers in answering the research question "How is oral health professional education reported in Europe?". The search strategy encompassed published literature searches, internet searches and further searching of relevant documents from educational organisations, regulators and professional bodies. Once the search strategy was developed, it was sent to key stakeholders for consultation. Sources were reviewed by two authors (JD, JF) and included in the review if they reported on oral health professional education in Europe. Results: A total of 508 sources were retrieved from all of the searches. A total of 405 sources were excluded as they did not report on the topic of interest, leaving 103 sources that reported on oral health professional education in Europe. Handsearching the references of published sources lead to a further 41 sources being screened, of which, 15 were included. In total, 33 duplications were removed and the final number of included sources was 85. The average year of publication for the included sources was 2007, with sources most commonly published in journals dedicated to dental education. Surveys represented the most common form of reporting. From the data obtained, four broad themes of reporting were evident: dental education at a programme level, dental education at a discipline level, other oral health professional education, and postgraduate education and continuous professional development. Conclusion: The reporting of dental and oral health professional education in Europe is limited. Whilst there are many useful documents that provide guidelines on dental education, there is limited knowledge on how education is implemented and delivered. There is a greater need for comprehensive educationally driven programme‐level data on oral health professional education across Europe.